KONVERGENSI IFRS DI INDONESIA Seberapa Perlunya Dilakukan di Indonesia dan Bagaimanakah Pelaksanaannya? - Andrea G. Diliharto G. Diliharto (Jurnal Akuntansi Bisnis, 2017)
The financial statements are often referred to as the language of business. The financial statements provide information about the company's financial condition that can be used as a basis for decision-making for all stakeholders of the company. Investors or shareholders, as a major stakeholder, is very concerned about the numbers and all of the information presented in the financial statements, considering all these things are intimately associated with the fate of their investment. The good financial statements will be able to convey the message of the report concerning the financial condition of the business entity so that it can be understood by the various interested parties (stakeholders). In order to uniformity of financial statements, they held a generally accepted standard. The financial statements must be presented shall be in accordance with accounting principles and generally accepted financial reporting or Generally Accepted Accounting Principles (GAAP). An accepted accounting principles in a country area in general is not necessarily accepted in other countries. Nature of "Generally Accepted" has a commonly accepted notion in a particular geographic area. In the development, the rapid globalization undermined the boundaries of demography and geography for potential investors and for traders to invest in running their business. This situation also leads to the formation of the financial system and global capital markets. The establishment of various regional and global capital markets such the New York Stock Exchange, London Stock Exchange, Singapore Stock Exchange, and others to accommodate the transactions between buyers and sellers from various backgrounds countries. This condition causes more eliminate the limitations in presenting the financial statements. GAAP is that we know today must be adapted to existing market conditions. It’s the origin of raising of International Financial Reporting Standards.Keyword : Konvergensi, Financial Reporting Standard (IFRS)